Reversing Fortunes of German Regions, 1926-2019: Boon and Bane of Early Industrialization? - Paul Berbée; Sebastian Till Braun; Richard Franke (ZBW - Leibniz Information Centre for Economics, 2022)
This paper shows that 19th-century industrialization is an important determinant of the significant changes in Germany's economic geography observed in recent decades. Using novel data on regional economic activity, we establish that almost half of West Germany's 163 labor markets experienced a reversal of fortune between 1926 and 2019, i.e., they moved from the lower to the upper median of the income distribution or vice versa. Economic decline is concentrated in northern Germany, economic ascent in the south. Exploiting plausibly exogenous variation in access to coal, we show that early industrialization turned from an advantage for economic development to a burden after World War II. The (time-varying) effect of industrialization explains most of the decline in regional inequality observed in the 1960s and 1970s and about half of the current North-South gap in economic development.
Keywords: N91; N92; O14; R12; 330; Industrialization; Economic development; Regional Inequality